Development of Arduino based smart home fire alarm system with emergency SOS notification - Rajinran K.R.; Choong P.Y.; Chua Y.L.; Alexander C.H.C. (American Institute of Physics, 2025)
This project aims to implement the application of Arduino smart fire alarm in real life situations. The project begun with research and system architecture design before prototyping. Phase 2 is developing the prototype using relevant sensors. Phase 3 focuses on the programming of the system where the commands are written in code form and executed to run the prototype. Four experiments were conducted to test the effectiveness of a prototype device designed to monitor temperature, humidity, and gas concentration in an environment. Experiment 1 revealed a significant difference in temperature and humidity between afternoon and night, with lower levels at night. Experiment 2 results showed that the prototype is effective in monitoring refrigerators and cold rooms. Experiment 3 demonstrated the DHT11's efficacy as both a temperature and humidity sensor. The final experiment, Experiment 4, tested the MQ-2 gas sensor's effectiveness in detecting smoke. The results showed that the prototype was able to detect smoke at a threshold of 300 ppm, and the alarm and RGB light functioned correctly. The system utilises various sensors to detect and respond to fire accidents in real-time, quickly containing them and alerting emergency services. The proposed method is cost- effective and offers an efficient solution for fire prevention in smart homes. ? 2024 Author(s).